Measuring sensor to cloud energy consumption - Azni A.H.; Rahman A.F.A.; Alwi N.H.M.; Seman K. (Association for Computing Machinery, 2024)
IoT devices must provide seamless connectivity while obeying stringent power and size constraints. Power consumption plays important factor to determine the status and connectivity of Sensor Node. This paper describes a series of simple experiments which measure the energy consumption of two IoT Sensor Nodes transmitting data to the cloud. The experiments will be used to compare the best solution between wire and wireless for IoT Sensor Nodes implementation. The experimental result shows that wireless connection consume more power compared to wire connection. Apart from comparison of two methods, the goal of this paper is also to develop a solid experimental basis, thus setting a better foundation for future research on IoT Sensor Nodes. 2017 ACM.